1998
DOI: 10.1557/proc-533-43
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Surface-Channel Strained Si1-yCyn-MOSFETS

Abstract: The first demonstration of n-MOSFETs fabricated using strained Si1-yCy surface channels is reported. Tensile-strained Si1-yCy layers with substitutional carbon contents up to 0.8 atomic percent were epitaxially grown on <100> Si substrates by rapid thermal chemical vapor deposition, using silane and methylsilane as the silicon and carbon precursors. n-MOSFETS were fabricated using standard MOS processing with reduced thermal exposure to minimize the possibility of strain relaxation. A remote plasma CVD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Looking for higher mobility materials is also a recent hot research topic [32][33][34]. Although mobilities of materials other than conventional Si, such as SiGe and strained Si, are quite attractive, the achievable channel mobility is still far below the universe curve of channel mobility for Si.…”
Section: Mobility Degradationmentioning
confidence: 99%
“…Looking for higher mobility materials is also a recent hot research topic [32][33][34]. Although mobilities of materials other than conventional Si, such as SiGe and strained Si, are quite attractive, the achievable channel mobility is still far below the universe curve of channel mobility for Si.…”
Section: Mobility Degradationmentioning
confidence: 99%
“…Fig. 7 compares the experimental mobility enhancement factor of strained Si 1−x C x n-MOSFETs on a Si substrate with a carbon content of 0.3% [20] and 0.4% [21]. The measured data for strained-Si 0.9975 C 0.0025 and Si 0.9954 C 0.0046 on Si 0.8 Ge 0.2 substrates are also shown.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Another advantage for future CMOS technology is the retardation of species outdiffusion from the source/drain into the strained-Si:C channel to improve short channel effect. However, recent results have indicated that Si 1−x C x has lower mobility [5] and reduces performance in a surface channel NMOSFET on relaxed Si buffers [5]. The goal of this work is to study the impact of carbon on device performance for strained-Si MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative enhancement factor is strongly correlated to the assumed alloy scattering potential for the calculations [2,3]. The Stanford group [4] has fabricated and demonstrated the operation of the surface channel of strained Si 1Àx C x NMOSFET, characterizing the electron inversion mobility both at room temperature and low temperature. However, it appears that the expected strain-induced phonon-limited mobility enhancement has been compensated for by the random alloy scattering and Coulomb scattering associated with non-substitutional carbon atoms [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Stanford group [4] has fabricated and demonstrated the operation of the surface channel of strained Si 1Àx C x NMOSFET, characterizing the electron inversion mobility both at room temperature and low temperature. However, it appears that the expected strain-induced phonon-limited mobility enhancement has been compensated for by the random alloy scattering and Coulomb scattering associated with non-substitutional carbon atoms [4]. Recently, the UT group demonstrated the buried channel strained Si 1Àx C x PMOSFET for the first time.…”
Section: Introductionmentioning
confidence: 99%